Implementation of Restorative Justice in the Legal Area of the State Attorney of Banjar Regency South Kalimantan - Anang Shophan Tornado; Soffyan Angga Fahlani; Nur Khalis Alfath; Nur Aida; Noor Fidhiatun Nisa; Risna Risna (International Journal of Law, Environment, and Natural Resources, 2023)
Restorative Justice is a criminal settlement that emphasizes justice and creates a balance between the rights of victims and perpetrators. The prosecution has a role to play as the main active element in conducting and creating a result that can resolve a crime and fulfil justice for the victim. This study examines how the enforcement and obstacles and barriers in the implementation of restorative justice as well as the ideal form of the application of restaurative justice in the territory of the State Prosecutor's Office of Banjar Regency Kalimantan South Province.